PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN BERBASIS ACCURATE BAGI UMKM - Safari, Ikmal Maulana; Nugroho, Bima; Al Fahri, Muhammad Fajar; Nazala, Muhammad Rizki; Damayanti, Prisila (PUAN INDONESIA, 2025)
This research focuses on introducing the use of Accurate accounting software for MSMEs in the Pondok Cina area. MSMEs are the backbone of the Indonesian economy, but face many obstacles in financial management. Accurate and structured financial reports are very important for business continuity and development. In the midst of the COVID-19 pandemic, mask MSMEs in Pondok Cina are experiencing rapid growth, but competition is also getting tougher. The ability to manage finances is a determining factor for success. Accurate offers solutions for recording transactions, creating financial reports, and analyzing financial data. The method used is education with a structured introduction and training approach. The stages include research/surveys, interviews, introduction to using the Accurate application, and basic training in making Accurate-based financial reports. This activity was carried out by directly visiting mask MSMEs in Pondok Cina. This research succeeded in providing understanding to mask MSMEs about the use of Accurate in preparing financial reports. Through training, business actors can understand the process of inputting transactions and producing financial reports such as profit and loss reports, capital changes reports, and financial position reports, as well as cash flow reports. The use of Accurate has proven to be beneficial for MSMEs in increasing the efficiency and accuracy of financial management. This training provides new knowledge and skills for business actors in managing finances professionally, so that they can improve the performance and desires of their business.